Validity and Usability of Physical Activity Monitoring in Patients with Chronic Obstructive Pulmonary Disease (COPD) - Boeselt, Tobias (PLoS One, 2016)
BACKGROUND: A large proportion of COPD patients do not achieve the recommended level of physical activity. It is suggested that feedback on the level of activity by using an activity monitoring device (PAM) increases awareness and may stimulate patients to increase their physical activity in daily life. Our objective was to assess the validity and usability of a simple and low-cost physical activity monitor (Polar A300(™)) when compared with the validated and established Bodymedia-SenseWear(™) (SWA) device. METHODS: To assess the diagnostic equivalent, two different PAM devices were used in parallel in 20 COPD patients GOLD I to IV during 3 consecutive days of daily life. Both systems were compared in terms of steps, calories burned, daily activity time and metabolic equivalents using linear regression analysis and Bland-Altman plots. Practical usability was examined by a 16-item-questionnaire. RESULTS: High correlations of both devices were observed with regard to the sensed step count (r = 0.96; p < 0.01) and calories burned (r = 0.74; p < 0.01), and a lower correlation of daily activity (r = 0.25; p < 0.01) was found. Data analysis over 3 days showed that 90% of the steps (95% CI -4223 to 1887), 100% of the calories (95% CI -2798 to 1887), 90% of the daily activity data (95% CI -12.32, 4065) and 95% of the MET (95% CI -3.11 to 2.75) were within the limits of agreement. A favorable usability (system-, information- and interface quality) of the A300(™) device was shown (p < 0.01). CONCLUSION: The A300(™) device with easy practical usability was shown not to be inferior for assessment of physical activity time, step count and calorie consumption in COPD patients when compared with the SWA. It is suggested to consider widespread available devices as commonly used for monitoring recreational sporting activities also in patients for assessment of physical activity in daily life.